Dynamic faces insights from experiments and computation - Curio, Cristobal; Bulthoff, Heinrich H.; Giese, Martin A. (MIT Press, 2011)
State-of-the-art research on the perception of dynamic faces, a topic of importance to brain, cognitive, and computational sciences.